2007
DOI: 10.3348/kjr.2007.8.2.111
|View full text |Cite
|
Sign up to set email alerts
|

Local Recurrence of Hepatocellular Carcinoma after Segmental Transarterial Chemoembolization: Risk Estimates Based on Multiple Prognostic Factors

Abstract: ObjectiveTo determine the prognostic factors for local recurrence of nodular hepatocellular carcinoma after segmental transarterial chemoembolization.Materials and MethodsSeventy-four nodular hepatocellular carcinoma tumors ≤ 5 cm were retrospectively analyzed for local recurrence after segmental transarterial chemoembolization using follow-up CT images (median follow-up of 17 months, 4-77 months in range). The tumors were divided into four groups (IA, IB, IIA, and IIB) according to whether the one-month follo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 25 publications
1
10
0
Order By: Relevance
“…In our results, the overall 1-year and 2-year local recurrence ratios were 8.3 and 16.7%, respectively. Our results were similar to those of Park et al [10] in the center of the liver segment. This could be due to obtaining 3D-safety margin in an adjacent area in cases with tumors located in a segmental or subsegmental border.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…In our results, the overall 1-year and 2-year local recurrence ratios were 8.3 and 16.7%, respectively. Our results were similar to those of Park et al [10] in the center of the liver segment. This could be due to obtaining 3D-safety margin in an adjacent area in cases with tumors located in a segmental or subsegmental border.…”
Section: Discussionsupporting
confidence: 93%
“…Previously, Park et al [10] reported that tumors located in the center of the liver segment showed lower recurrence ratio of 13.3% when compared with tumors located in a segmental border zone of 44.8% during the median follow-up period of 17 months. In our results, the overall 1-year and 2-year local recurrence ratios were 8.3 and 16.7%, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…7,12 A study from Korea reported a higher rate of recurrence than our study (22.4%). 13 Currently, HCC is one of the major indications for OLT, with expected recurrence rates between 15% to 20% and less than 10% in patients who meet the Milan criteria, and overall survival rate of patients within Milan criteria is over than 70% after liver transplant. 10,14 In patients in our study, the tumorfree survival rate for tumors within Milan criteria was 83.9% and beyond Milan criteria was 69.2%.…”
Section: Discussionmentioning
confidence: 99%
“…There is increasing evidence that selective TACE achieves better antitumoral effects and reduces both the dosage of drugs used for TACE and the number of TACE sessions needed to achieve extensive tumor necrosis as compared to the use of conventional TACE (8-11). …”
Section: Basic Principles Of Transarterial Chemoembolizationmentioning
confidence: 99%